iPhone Games Projects - Cabrera, PJ (Apress, 2012)
First, the obvious: the iPhone rocks. Less obviously, so does the iPod touch—no phone, no cellular network (and the associated monthly fee), just a wonderful game-playing, application-downloading, insanely great Cocoa touch machine. Consumers love them both for their stability, ever-present network access, ineffable coolness, and (as we developers know firsthand) all of those great third-party apps. Apple’s App Store rocks, too, and as the owners of these devices have made it clear, games rock the most! The Wall Street Journal reported data from Mobclix showing that over a quarter of the applications in Apple’s App Store are games (see http://blogs.wsj.com/digits/ 2009/03/23/no-recession-for-iphone-game-apps/). Venture capitalists are getting in on the action as well, financing game developer Ngmoco to the tune of $10 million. There has even been a conference devoted to gaming on the iPhone (see http://www.igsummit.com/). Think of this book as a guide and companion through your personal journey of game development for the iPhone and iPod touch. And like any good travel guide, it’s full of tips, highlights, and invaluable suggestions for avoiding the costly and time-consuming mistakes of the early explorers who have gone before you.